Influence of thermal cycles and disinfection on the roughness, microhardness and color of PETG/TPU and PMMA. - Neto, Clóvis Lamartine De Moraes Melo [UNESP]; Bernardi, Bruno Simão [UNESP]; Dekon, Stefan Fiuza De Carvalho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Goiato, Marcelo Coelho [UNESP] (Wroclaw Medical University, 2023)
BACKGROUND: Occlusal splints can protect teeth during bruxism, preventing tooth wear, as well as during sports activities, shielding them from impacts. OBJECTIVES: To verify the influence of thermal cycles and disinfection on the roughness, microhardness and color of polyethylene terephthalate glycol/thermoplastic polyurethane (PETG/TPU) and poly(methyl methacrylate) (PMMA). MATERIAL AND METHODS: Thirty-six PETG/TPU samples and 36 PMMA samples were prepared (ø10 mm × 3 mm). Six groups were created according to the material and the disinfection method used (n = 12 each): PETG/TPU (glister), PETG/TPU (hypochlorite), PETG/TPU (soap), PMMA (glister), PMMA (hypochlorite), and PMMA (soap). Roughness, Knoop microhardness and color evaluations were performed before the experiments (T1), after thermocycling (T2) and after disinfection (T3). Three-way repeated measures analysis of variance (ANOVA) and Tukey's test were used for statistical evaluations. RESULTS: For roughness and color, ANOVA showed statistical significance based on the interaction between thermal cycling, material and disinfectant factors. In terms of Knoop microhardness, ANOVA showed statistical significance based on the interaction between thermal cycling and material factors. CONCLUSIONS: Roughness results were clinically acceptable in all groups at all time points, except the PETG/TPU and PMMA groups disinfected with hypochlorite. Microhardness significantly increased for both materials after thermal cycling, and at all time points, the microhardness of PMMA was significantly higher than that of PETG/TPU. After thermal cycling, the color changes were clinically unacceptable in all groups.